Reducing Antimicrobial Use and Dependence in Livestock Production Systems: A Social and Economic Sciences Perspective on an Interdisciplinary Approach - Baudoin, Fanny; Hogeveen, Henk; Wauters, Erwin (Frontiers in Veterinary Science, 2021)
Objective: AMR is considered an externality as it is the undesired result of preventive and curative antimicrobial use. To address this biosocial issue, our objective is to work towards a trans- or interdisciplinary research agenda by looking at research that is needed to develop effective and efficient policies and strategies to address AMR in livestock. Method: We address AMR with concepts developed for agricultural environmental pollution problems and describe how policies and strategies can be developed by defining (a) who, (b) what and (c) how to target. To identify key actors in antimicrobial decision-systems, systemic approaches such as value chain analysis and a framework for the analysis of agricultural innovation systems were used to get insights at both micro and macro level. Moreover, we zoom in on the production part of the value chain and describe the contribution of livestock farmers to AMR as well as the influence that other actors or external factors may have on this contribution to identify optimal bases to formulate interventions and to measure compliance with these interventions. We then define how voluntary or compulsory behavioral change can be achieved via five routes and finally present three criteria for ex-ante analysis and ex-post evaluation of policies and strategies. Conclusion: Systemic approaches allow to comprehensively characterize antimicrobial decision system, hence identifying a) all actors influencing AMU at the farm level, b) adequate regulatory and intervention bases (i.e., AMU, animal health status, biosecurity, production systems, meat, etc.), c) what behavioral change strategy to use and d) whom should implement this. In addition, cost-effective analyses are needed to identify the best combinations of routes since economic and time resources are limited. Finally, we advocate for transdisciplinary or at least interdisciplinary work to address AMR, since policies and strategies within the five behavioral change routes are often investigated within different disciplines and not in a holistic and systemic way